Quantitative Diagnosis of Arrhythmia by the Serial Scatter Diagrams of RR-Interval - BABA, Yasumasa; KATO, Takao; KOMAZAWA, Tsutomu (Iyo denshi to seitai kogaku, 1980)
This paper presents an approach to the computerized quantitative diagnosis of arrhythmia from the point of view of mathematical statistics. We propose a method in which serial scatter diagrams of RR-interval in electrocardiogram are used. We have found that the use of the diagrams for classification of arrhythmias was effective. Therefore, we devised the method of automated diagnosis in which arrhythmia was recognized from the patterns in the diagrams. The usefulness of the method was proved by comparing the results of diagnosis processed by this computer method on the controlled and arrhythmia subject with those performed by decision of medical doctors (cardiologists). These results are quite satisfactory, and this method may be made available for clinical examinations.